Edukasi Perawatan Luka Pasca Operasi untuk Mencegah Infeksi - Suaib Suaib; Kurnia Mariatul Qiftih; Iin Fadhilah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Postoperative wound care is a crucial part of the healing process and infection prevention. Lack of knowledge among patients and families regarding proper wound care can increase the risk of surgical wound infections. This community service activity aims to improve the knowledge and skills of patients and families in performing postoperative wound care independently and correctly. The activity included counseling, interactive discussions, demonstrations, and hands-on practice. The results of the activity indicated an increase in participants' understanding of the principles of postoperative wound care and infection prevention. This activity is expected to increase patient independence in wound care and reduce the risk of postoperative infection.